Biblioteki klasztorne na łamach „Naszej Przeszłości”. Zarys problematyki - Warząchowska, Bogumiła (Archiwa, Biblioteki i Muzea Kościelne, 2011)
„Our Past” is a periodical with plenty of interesting monographs, treatises, articles and reviews covering a wide range of issues and problems, which for years had an influence on the culture-forming development of the history of the Church in Poland. Analyzing the thematic content of “Our Past”, it can be noticed that in its pages there are a great number of articles on the religious orders and monastic life. The texts often focus on the organizational structure of the monastery, monastic and everyday life. The issue of books and monastic libraries is touched on only marginally. However, the analysed documents reveal that each monastery had at least one small library. Larger monasteries boasted rich collections of books. “Our Past” presents the libraries of the Basilians, Dominicans, Franciscans, Capuchins, Missionary Priests, Benedictines, Cistercians, Canons Regular. It also contains the material on convent libraries, among others, the ones of Bridgettines and female monastic schools. It should be emphasized that the studied articles are characterized by extremely broad scientific apparatus based on archive material and source documentation. Plenty of texts include a rich set of illustrations and photographs, which contributes to the vivid presentation of the mentioned issues.